2018
DOI: 10.1155/2018/1651097
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method to Quantify Longitudinal Orthodontic Bone Changes with In Vivo Micro-CT Data

Abstract: Orthodontic tooth movement (OTM) is the result of region-specific bone modeling under a load. Quantification of this change in the alveolar bone around a tooth is a basic requirement to understand the mechanism of orthodontics. The purpose of this study was to quantify subregional alveolar bone changes during orthodontic tooth movement with a novel method. In this study, 12 Sprague-Dawley (SD) rats were used as an orthodontic model, and one side of the first upper molar was used to simulate OTM. The alveolar b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…This indicates that there has been remodeling of the alveolar bone that was dominated by bone resorption. This is in line with research conducted by Wang et al 7 in mice using a closed coil spring which shows a decrease in bone mineral density on days 3 to 14 and returns to normal on day 28. A decrease in bone mineral density in the control group is likely due to the mechanical induction of orthodontics to stimulate osteoblasts to release RANKL and M-CSF which then binds to c-Fms and RANK on osteoclast precursors so that osteoclast differentiation and activation occurs for bone resorption.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This indicates that there has been remodeling of the alveolar bone that was dominated by bone resorption. This is in line with research conducted by Wang et al 7 in mice using a closed coil spring which shows a decrease in bone mineral density on days 3 to 14 and returns to normal on day 28. A decrease in bone mineral density in the control group is likely due to the mechanical induction of orthodontics to stimulate osteoblasts to release RANKL and M-CSF which then binds to c-Fms and RANK on osteoclast precursors so that osteoclast differentiation and activation occurs for bone resorption.…”
Section: Discussionsupporting
confidence: 93%
“…Osteoclasts play a role in alveolar bone surface resorption by forming an acidic environment that causes bone demineralization and collagen matrix degradation, while osteoblasts play a role in bone formation through collagen secretion and glycoprotein to form osteoids. 7 Osteoclasts are regulated by two major cytokines, namely macrophage colonystimulating factor (M-CSF) and RANKL produced by osteoblasts that bind to osteoclasts receptors, namely c-Fms and RANK. 8 Chocolate (Theobroma cacao) is a processed cocoa product that has a diverse mixture of chemical compounds.…”
Section: Introductionmentioning
confidence: 99%
“…3D evaluation premises reliable image segmentation which can be particularly challenging when metal artifacts are present, or when histograms overlap. [16][17][18][19][20] Since mineral contents of cementum and bone were reported to be likewise [21], reliable approaches to segment tooth roots in μCT are an inevitable premise for volumetric assessment of OTM and RR in μCT.…”
Section: Introductionmentioning
confidence: 99%
“…Although the measurements became more and more accurate, the evaluation of the dynamic changes induced by OF still remains di cult, as it is hard to nd a reliable reference structure. Previous studies in rats evaluated OTM in an indirect way based on external reference structures such as the contralateral maxilla (splitmouth designs) [19,31] , the incisors [28,32] , the zygomatic arch [17] or the diastema formed between the rst and the second molar [10,15,[33][34][35][36] . However, these methods rely on those reference structures remaining stable during OTM.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the dynamic change in alveolar bone when applying a constant orthodontic force remains largely unknown. Although previous animal research showed changes in the bone mineral density (BMD) of alveolar bone subjected to orthodontic force [14,15] , few studies performed complete longitudinal bone morphometric assessment [16] [17] . Whether there is a correlation between the dynamic changes in OTM rate and the changes in bone morphometric parameters still needs to be elucidated.…”
Section: Introductionmentioning
confidence: 99%